2015
DOI: 10.7439/ijbr.v6i5.2068
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of ectopic pregnancy in a tertiary care centre in South Kerala

Abstract: Introduction: Ectopic pregnancy means the presence of pregnancy outside the normal uterine cavity. Ectopic pregnancy commonly occurs in the fallopian tube (95 %). Diagnosis can be made by USG, serum hCG, although the 'gold standard' is laparoscopy. Management of the cases depends on the clinical presentation, site of the ectopic and need for future reproductive function and can be medical as well as surgical. Objectives: To determine the incidence of ectopic pregnancy, to assess the percentage of ectopic pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Similar to our study, most studies reported that majority of women diagnosed with ectopic pregnancy belonged to this age group. 7,[9][10][11][12][13][14][15][16]18,19 This is probably because sexual activity and fertility of women is highest during this period. In the present study, 70% of the women were multiparous which was comparable with studies by Bhuria et al, Rakhi et al, Yadav et al and Prasanna et al 8,15,18,19 In the present study, the commonest site for ectopic pregnancy was tubal (92%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, most studies reported that majority of women diagnosed with ectopic pregnancy belonged to this age group. 7,[9][10][11][12][13][14][15][16]18,19 This is probably because sexual activity and fertility of women is highest during this period. In the present study, 70% of the women were multiparous which was comparable with studies by Bhuria et al, Rakhi et al, Yadav et al and Prasanna et al 8,15,18,19 In the present study, the commonest site for ectopic pregnancy was tubal (92%).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] This shows that early diagnosis, timely and prompt management of ectopic pregnancy, availability of adequate blood and blood components improves the outcome of ectopic pregnancies. Delay in seeking healthcare, accessibility to expert health facilities, initial misdiagnosis and delayed referral are important deterrents to prompt management of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 75 % of women were in the age group of 20-35 years. Similarly many studies reported that majority of women diagnosed with ectopic pregnancy belonged to this age group (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This is probably because this age group is the period of highest sexual activity and fertility.…”
Section: Discussionmentioning
confidence: 89%
“…Yeasmin S et al 22,26,32 UPT was found to be negative in 6 cases (13.33%) relatable to 6% in studies by Prasanna B et al 31 Culdocentesis was done in 6 cases (13.33%) kindred to studies by Gupta V (16%), Gaddagi R (37.8%), Ganitha (40%) et al 11,13,33 The first successful ultrasound diagnosis of ectopic pregnancy was reported by Kobayashi in 1969. Nearly 86.67% of patients had documented ultrasound findings of echogenic adnexal mass relatable to 83%, and 84% of Nair L and Wakankar et al 19,34 Hemoperitoneum was visualised in 29 patients (64.44%) similar to 62.5%, 66.6% of Debnath J ,Sudha VS et al 17,35 Gestational sac in adnexa was appreciated in 17.78% (n = 8) of individuals akin to 11%, 14% in studies by Mooij, Ganitha G et al 5,13 Ectopic cardiac activity was detected in four patients (8.89%) homologous to 12.5%, 16% in studies by Debnath J, Shetty VH et al 18,35 Pseudo gestational sac was noted in 4.4% patients corresponding to 12%,16% of studies by Debnath J, Shetty VH et al 18,35 Rudimentary horn was seen in 4.4% patients analogous to 9.1% in studies by Gaddagi R et al 11 The classical triad of amenorrhoea, pain abdomen, bleeding per vaginum was discerned in 23 women (51.11%) corresponding to 48%, 53.84%, 54.2%, of Karmakar, Wakankar, Soren M et al 15,19,20 History of amenorrhoea was seen in 88% equivalent to 84%, 86.25%, 88%, 88.09% of Shalini, Mehta A, Shetty VH, Pranathi et al 7,12,16,18 About 86% of ectopic patients presented with pain abdomen kindred to studies by Sudha VS (82.4%), Wakankar (86.53 %), Shetty VH (88%), Most. Sabina Yeasmin (89%) et al [17][18][19]32 Bleeding per vaginum was perceived in 66% of patients homogenous to 63.3%, 63.5%, 65.3%, 68% of studies of Sudha VS, Most.…”
Section: Resultsmentioning
confidence: 96%